Financial sustainability of Malaysian public universities: officers’ perceptions - Nik Ahmad, Nik Nazli; Ismail, Suhaiza; Siraj, Siti Alawiah (Emerald Group Publishing Ltd., 2019)
Purpose – The purpose of this paper is twofold: first, to elicit perceptions of senior officers on the overall financial sustainability of their institutions; and, second, to examine senior officers’ perceptions on important revenue diversification and cost management practices. Design/methodology/approach – The study employed a questionnaire survey with senior academic and administrative staff of the 20 public universities in Malaysia. In total, 275 questionnaires were distributed and 69 were returned, yielding a response rate of 25.09 per cent. Descriptive statistics were used to analyse the general perceptions of the survey respondents on public university financial sustainability issues. Findings – The study suggests that respondents are receptive of the financial sustainability challenges faced by their institutions. Respondents agree that increasing tuition fees may not be a feasible revenue enhancement strategy for public universities. Instead, all respondents agree that full utilisation of resources will be a key strategy that the universities can apply. Originality/value – This study contributes to the limited research on the financial sustainability of public universities in developing countries. Findings of the study have implications for the financial management and governance of public universities in Malaysia and other countries facing similar fiscal challenges. The findings of the study also provide important empirical evidence for future work in the area.